Apakah Status Akreditasi Rumah Sakit Memberikan Perbedaan Pemberian Obat yang Benar dan Keselamatan Pasien? - Saptono Putro; Viera Wardhani; Siswanto Siswanto (Media Kesehatan Masyarakat Indonesia, 2018)
Hospital accreditation provides guidelines for implementing quality management standards including drugmanagement management to reduce the incidence of patient safety (IPS). This study aims to determine the differencebetween the right implementation of drug administration and the perceieved of IPS based on hospital accreditationstatus. This researchusing a survey method with cross sectional analytical approach, which compares thecorrect implementation of the drug and IKP perception in 2 type D hospitals with different accreditation status inthe Greater Malang area. Measurements of the correct implementation of drug administration and IKP perceptionswere carried out using a closed questionnaire on 36 nurses and 99 primary hospital patients and 41 nursesand 96 full hospital patients. Analysis was carried out by Mann Whitney Z test and Rank Spearman test. Bothhospitals showed the correct level of implementation of good drug delivery and low IPS perception even thoughthe first accredited hospital showed a better picture than plenary accredited hospitals. In hospitals with initialaccreditation shows that the better the right implementation of drug administration, the lower the perception ofIPS according to nurses and patients. There was no similar relationship in the hospital with full accreditation status,where there was no difference in the level of true implementation of drug administration and IKP perceptionaccording to nurses and patients.